The resounding of the drums of the Military-Civil Dictatorship in Brazil: The tortures, the persecutions against Dom Hélder Câmara and the murder of Father Henrique - Bandeira, Élcia de Torres (Seven Editora, 2024)
Nothing seems more absurd than the resounding resounding cries of pain in the face of the war arsenal that is often used as a silencer of the facts and contrary arguments that are raised in the sense of awareness and social mobilization for the well-being of all indiscriminately on the banks of the Ipiranga, the Capibaribe, the Beberibe or even the Jordan River. Remembering and repudiating the tortures, the murder of Father Henrique and the attacks and persecutions against Dom Hélder Câmara in Recife is necessary for understanding popular religiosity in Brazil and the tortuous paths that the Catholic Church took during the military-civil dictatorship in the country. Under the hallucinatory rhythm of the military's drumming, human bodies became drums emitting out-of-tune sounds. The impunity of crimes and the symbolic representations associated with them demand reflection and denunciation. Silence also becomes a crime due to the inertia of complicity. History and Justice are responsible for ascertaining the facts. DOI:https://doi.org/10.56238/sevened2024.018-038